2004
DOI: 10.1016/j.febslet.2004.11.111
|View full text |Cite
|
Sign up to set email alerts
|

Combining data from genomes, Y2H and 3D structure indicates that BolA is a reductase interacting with a glutaredoxin

Abstract: Genomes, functional genomics data and 3D structure reflect different aspects of protein function. Here, we combine these data to predict that BolA, a widely distributed protein family with unknown function, is a reductase that interacts with a glutaredoxin. Comparisons at the 3D structure level as well as at the sequence profile level indicate homology between BolA and OsmC, an enzyme that reduces organic peroxides. Complementary to this, comparative analyses of genomes and genomics data provide strong evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 39 publications
4
85
1
1
Order By: Relevance
“…In bacterial operons, BolA tends to occur not only with a monothiol glutaredoxin, but also with proteins involved in defense against oxidative stress: glutathione-S-transferase and Toluene exporters (16). We found, however, no evidence for upregulation of BOLA1 under conditions of oxidative stress in human gene expression data (Supplementary Table S2).…”
Section: Willems Et Alcontrasting
confidence: 43%
See 3 more Smart Citations
“…In bacterial operons, BolA tends to occur not only with a monothiol glutaredoxin, but also with proteins involved in defense against oxidative stress: glutathione-S-transferase and Toluene exporters (16). We found, however, no evidence for upregulation of BOLA1 under conditions of oxidative stress in human gene expression data (Supplementary Table S2).…”
Section: Willems Et Alcontrasting
confidence: 43%
“…Here we provide first evidence that BOLA1 might exert such a role and that one of the target proteins of the BOLA1/GLRX5 complex is involved in maintaining the normal mitochondrial shape. It should thereby be noted that, although BolA's 3D structure is similar to that of the bacterial reductase OsmC, suggesting a reducing activity of BolA itself, BolA1 does not contain any conserved cysteines, rendering any reducing function dependent on an external source of reducing equivalents (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fra2 is a member of a protein family of unknown function, which is named after one of the E. coli members, BolA. BolAlike proteins have been hypothesized to work together with monothiol glutaredoxins based on computational and biochemical analyses (28). Recently, a chloroplast-localized protein homologous to BolA was identified that participates in chloroplast Fe-S synthesis of Arabidopsis thaliana (29).…”
Section: Discussionmentioning
confidence: 99%